2022
DOI: 10.11124/jbies-21-00436
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive capacity in the adoption of innovations in health: a scoping review

Abstract: The objective of this scoping review was to explore how absorptive capacity has been conceptualized and measured in studies of innovation adoption in health care organizations.Introduction: Current literature highlights the need to incorporate knowledge translation processes at the organizational and system level to enhance the adoption of new knowledge into practice. Absorptive capacity is a set of routines and processes characterized by knowledge acquisition, assimilation, transformation, and application. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…The high correlation (>0.7) between the burnout scale and mental health scale in our study was indeed slightly higher than that reported in other studies (Godfrey et al, 2021), which may reflect the same variable or strong correlation between burnout and mental well-being during the pandemic. Similar to many studies, our study found that burnout significantly affected mental health (Koutsimani et al, 2019) and played a mediating role in the relationship between job stressors (Huang et al, 2022;Zhou et al, 2022) and COVID-19-related concerns and mental health and well-being (Ahorsu et al, 2022;Babamiri et al, 2022; Chen et al, 2020).…”
Section: Discussioncontrasting
confidence: 63%
“…The high correlation (>0.7) between the burnout scale and mental health scale in our study was indeed slightly higher than that reported in other studies (Godfrey et al, 2021), which may reflect the same variable or strong correlation between burnout and mental well-being during the pandemic. Similar to many studies, our study found that burnout significantly affected mental health (Koutsimani et al, 2019) and played a mediating role in the relationship between job stressors (Huang et al, 2022;Zhou et al, 2022) and COVID-19-related concerns and mental health and well-being (Ahorsu et al, 2022;Babamiri et al, 2022; Chen et al, 2020).…”
Section: Discussioncontrasting
confidence: 63%
“…1(p.128) In 2002, Zahra and George 2 expanded on this definition to emphasize the active process of transforming and exploiting that new knowledge. 3 Their extended definition provided the basis for the 4 components of absorptive capacity: i) identify the new knowledge, ii) assimilate the knowledge, iii) integrate the knowledge into the existing knowledge base, and iv) use the new knowledge to change the organization in some way. 3 The concept of absorptive capacity has its origins in biology 4 and refers to the capacity of the gastrointestinal tract to absorb digested nutrients into the body.…”
mentioning
confidence: 99%
“…3 Their extended definition provided the basis for the 4 components of absorptive capacity: i) identify the new knowledge, ii) assimilate the knowledge, iii) integrate the knowledge into the existing knowledge base, and iv) use the new knowledge to change the organization in some way. 3 The concept of absorptive capacity has its origins in biology 4 and refers to the capacity of the gastrointestinal tract to absorb digested nutrients into the body. Somehow, this term leaked out of the gut and has been adopted by the business world where it is used to help understand and monitor an organization's capacity to absorb new or innovative knowledge.…”
mentioning
confidence: 99%
See 2 more Smart Citations